THE PROJECT «ONE BELT, ONE WAY»: CHINESE GEOSTRATEGY - Дем’янчук, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
This article reviews the project of the People’s Republic of China "One Belt, One Way." The Chinese side has already announced the allocation of more than 40 billion dollars. USA to implement large-scale infrastructure projects. Today, the development of new transport corridors with the participation of European states depends on the realization of not only their transit potential, but also the stabilization of the region’s economy as a whole through the development of political and economic cooperation mechanisms. Ukraine has a unique chance to join this initiative and contribute to the creation of a new economic order in Europe, Asia and Africa. Delaying the definition of national priorities in this direction can lead to its removal from strategic decisions on the development of mutually beneficial regional relations. The key task for the Ukrainian Government is to accelerate the pace of economic reform, which will provide clear and transparent rules of the game for all interested parties and significantly improve the investment climate in Ukraine.